2000
DOI: 10.1001/archpedi.154.12.1248
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Adolescents' Aggressive and Hostile Behaviors

Abstract: Brief family competency-training interventions designed for general populations can reduce aggressive and hostile behaviors in adolescents' interactions with parents and adolescent aggressive behaviors outside of the home setting. Thus, this type of intervention has important public health implications. Arch Pediatr Adolesc Med. 2000;154:1248-1257.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 50 publications
4
48
0
Order By: Relevance
“…The initial measurements support previous fi ndings that girls with bullying behavior often were bullying victims themselves [23] , show relatively high violence-related behavior and sexual risk-taking behavior levels [4,5,[24][25][26] and anger levels [10,19] , in addition to disturbed interpersonal relationship patterns [11,20] . Their initial general health perceptions, vitality, social functioning, role limitations resulting from emotional problems and mental health were distinctly below normal values [8,21] .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The initial measurements support previous fi ndings that girls with bullying behavior often were bullying victims themselves [23] , show relatively high violence-related behavior and sexual risk-taking behavior levels [4,5,[24][25][26] and anger levels [10,19] , in addition to disturbed interpersonal relationship patterns [11,20] . Their initial general health perceptions, vitality, social functioning, role limitations resulting from emotional problems and mental health were distinctly below normal values [8,21] .…”
Section: Discussionsupporting
confidence: 80%
“…Treatments for aggression should generally combine pharmacological agents [9,10] and environmental or psychotherapeutic (as well as family therapeutic) [11][12][13] measures. The degree of family confl ict, domestic violence, and family support have a critical infl uence on the extent of this problem [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…The study also confirms the results of research conducted by other authors who described the effectiveness of outpatient family therapy. [15][16][17][18][19]21 …”
Section: E250mentioning
confidence: 99%
“…10 The degrees of family conflict, domestic violence, and family support all have a critical impact on the extent of the problem. 11 Treatment for aggression is based on the underlying causes and should generally combine pharmacologic [12][13][14] and environmental or psychotherapeutic (as well as family therapeutic) [15][16][17][18][19] measures.…”
mentioning
confidence: 99%
“…The findings showed that the intervention with family involvement achieved a 35% reduction in felonies, a 30% reduction in violent crime, and a 21% reduction in misdemeanors. Similarly, brief interventions aimed at improving family mediation skills may reduce not only the incidence of hostile interactions between parents and young people in the home, but also the incidence of violent or aggressive behavior by young people outside the home, as demonstrated by the Iowa Strengthening Families Program (Spoth et al, 2000). A US study by Terzian et al (2011) identified effective strategies for reducing risky behaviors, through a meta-analysis of 123 programs designed to prevent or reduce aggressive behavior, with direct impacts determined through experimental evaluations.…”
Section: B) Programs For Youth At Greater Risk Work Best When They Comentioning
confidence: 99%